2010
DOI: 10.3238/arztebl.2010.0361
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Urinary Tract Infection

Abstract: With the aid of a small number of additional diagnostic criteria, antibiotic treatment for UTI can be provided more specifically and thus more effectively. Differentiating UTI from asymptomatic bacteriuria, which usually requires no treatment, can lower the frequency of unnecessary antibiotic prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
303
1
19

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(365 citation statements)
references
References 33 publications
8
303
1
19
Order By: Relevance
“…1B) can be used for real time bacterial density determination (for example, in a urine sample). Within 30 s, it would be possible to assess if it was a severe bacterial infection with more than 10 5 cells per 1 mL, and within 10 min, it would be possible to determine if there is a clinically relevant infection at all (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…1B) can be used for real time bacterial density determination (for example, in a urine sample). Within 30 s, it would be possible to assess if it was a severe bacterial infection with more than 10 5 cells per 1 mL, and within 10 min, it would be possible to determine if there is a clinically relevant infection at all (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…Prompt and efficacious treatment of symptomatic UTIs is warranted in pregnant women. Nevertheless, there is still some controversy regarding the screening and treatment of asymptomatic forms during gestation (Lin and Brown 2010;Lumbiganon et al, 2010;Schmiemann et al, 2010). Given the prevalence and the potential impacts of UTIs on the health of the mother and her child, the objective of this chapter is to cover the most important clinical aspects of the epidemiology, etiology, physiopathology, pregnancy outcomes, and the treatment risks and benefits associated with UTIs during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The rationale of these studies is to provide clinicians with a clinical decision rule to improve the quality of UTI care. 4,5 McIsaac et al have shown that the application of a simple diagnostic algorithm can result in the correct treatment of most females with UTI and can reduce unnecessary urine culture testing and antibiotic prescriptions.…”
Section: Introductionmentioning
confidence: 99%